Typical scheme of USS forces reaction on disasters with emission of strong poisonous substances which predetermines the operative level of service-combat actions of the Interior Troops - Antonets, V. V.; Babkov, Yu. P.; Ermoshyn М. О. (Honor and Law, 2019)
The actions of law-enforcement forces are classified in the form of service-combat actions as operative application. This article gives typical scheme of reaction of forces of Uniform state system of prevention and reaction to emergency situations of technical and natural character (USS) on disasters with emission (emission threat) of strong poisonous substances. This scheme predetermines the operative level of service-combat actions of the Interior Troops.